DEVELOPMENT OF THE LEARNING TOOLS VISIONARY SETS MATERIAL COORDINATION SYSTEM - Chotimah, Nurul (BIOMA, 2011)
Teachers, as facilitators should be creative in designing the learning process. One design alternative that can be used is a learning process oriented SETS. The study aims to determine the role of learning in biological vision SETS in-crease student learning outcomes biology of MAN Lasem Rembang. Research is a research and development (R & D), Kemp model. The study was done in two stages. The first stage is the stage of development of the device and the second stage is the stage of real learning. The results showed an increase in student learning outcomes, activity, process skills, a positive response from students and teachers, and student learning outcomes. The conclusion is, the development of learning tools SETS vision was in-strumental and helpful in the learning process and student learning outcomes on the subjects of biology. Key words: learning tools, SETS, coordination systems, multimedia, learning outcomes